The relationship between earnings and cash flows with dividends / Norilmiah Azis - Azis, Norilmiah (2001)
The objectives of this study is to identify whether there are a significant relationship between earnings and cash flows with dividend changes for companies listed on the Main Board of the Kuala Lumpur Stock Exchange (KLSE) and to examine the effect of dividend changes, current earnings and current cash flows as predictors of future earnings. Samples of the study consists of 70 companies listed on the Main Board of the Kuala Lumpur Stock Exchange. Correlation and Regression Analysis are used to analyse the accounting data for the period 1990 — 1996 obtained from the Corporate Handbook Malaysia. The findings indicate that only change in earnings is positively and significantly associated -with dividend changes. The other variables are not significantly associated with dividend changes. The findings also reveal that there is no support for the notion that there exists a positive association between dividend increases and future earnings. However, current earnings and current cash flows are significant explanators and are the key predictors of future earnings.